Marine Actinomycetes, New Sources of Biotechnological Products - Jagannathan, Sveta V. (Mar Drugs, 2021)
The Actinomycetales order is one of great genetic and functional diversity, including diversity in the production of secondary metabolites which have uses in medical, environmental rehabilitation, and industrial applications. Secondary metabolites produced by actinomycete species are an abundant source of antibiotics, antitumor agents, anthelmintics, and antifungals. These actinomycete-derived medicines are in circulation as current treatments, but actinomycetes are also being explored as potential sources of new compounds to combat multidrug resistance in pathogenic bacteria. Actinomycetes as a potential to solve environmental concerns is another area of recent investigation, particularly their utility in the bioremediation of pesticides, toxic metals, radioactive wastes, and biofouling. Other applications include biofuels, detergents, and food preservatives/additives. Exploring other unique properties of actinomycetes will allow for a deeper understanding of this interesting taxonomic group. Combined with genetic engineering, microbial experimental evolution, and other enhancement techniques, it is reasonable to assume that the use of marine actinomycetes will continue to increase. Novel products will begin to be developed for diverse applied research purposes, including zymology and enology. This paper outlines the current knowledge of actinomycete usage in applied research, focusing on marine isolates and providing direction for future research.